Pengembangan E-Modul Bahasa Arab Berbasis Contextual Teaching and Learning Pada Materi Al-‘Unw’ānu Kelas VII MTs PPM Al-Ikhlash Sulawesi Barat / Development of Arabic Language E-Modules Based on Contextual Teaching and Learning on Al-‘Unw’ānu Material for Class VII MTs PPM Al-Ikhlash West Sulawesi - An Ghifaria Ayu; Darmawati Darmawati; Herdah Herdah (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
This study discusses the development of contextual Arabic language e-modules on the material of al-'unwānu. This is based on various problems found in the Arabic language learning process in an era of rapid and rapid technological development that requires innovation to be developed, one of which is the development of e-modules with an attractive appearance and more detailed material. This study aims to describe the prototype design of the learning e-module, the level of validity and effectiveness. The research method used is Research and Development by adapting Sugiyono's development steps, namely: (1) potential and problems; (2) data collection; (3) product design; (4) validation; (5) design revision; (6) product trial; (7) product revision; (8) usage trial; (9) product revision; (10) mass production. The results of this study are contextual Arabic language e-modules that are interesting and suitable for use to improve student understanding in learning. The validity of the e-module is very valid with a percentage of material expert I scores of 88%, material expert II 82%, media expert 80%, learning expert 96% and student response 91%. The level of effectiveness of the e-module is in the category of 'quite effective' with the results of the effectiveness test of student understanding obtained an average initial test score = 41.2 final test = 79.36, the difference between the initial and final test scores = 38.16. The result of the n-gain score calculation is 0.649573338 with a presentation of 65%. So that the contextual Arabic language learning e-module on the al-'unwānu material is quite effective to be used to improve student understanding.Abstrak: Penelitian ini membahas tentang pengembangan e-modul bahasa Arab berbasis kontekstual pada materi al-‘unwānu. Hal ini didasari pada berbagai persoalan yang didapat dalam proses pembelajaran bahasa Arab di zaman berkembangnya teknologi dengan pesat dan cepat yang mengharuskan adanya inovasi yang dikembangkan salah satunya dengan pengembangan e-modul dengan tampilan yang menarik dan materi yang lebih rinci.  Penelitian ini bertujuan untuk mendeskripsikan prototipe desain e-modul pembelajaran, tingkat validitas dan efektifitas. Metode penelitian yang digunakan ialah penelitian dan pengembangan dengan mengadaptasi langkah pengembangan Sugiyono, yaitu: (1) potensi dan masalah; (2) pengumpulan data; (3) desain produk; (4) validasi; (5) revisi desain; (6) uji coba produk; (7) revisi produk; (8) uji coba pemakaian; (9) revisi produk; (10) produksi massal. Hasil penelitian ini ialah e-modul bahasa Arab berbasis kontekstual yang menarik dan layak digunakan untuk meningkatkan pemahaman siswa dalam pembelajaran. Validitas e-modul sangat valid dengan presentase nilai ahli materi I 88%, ahli materi II 82%, ahli media 80%, ahli pembelajaran 96% dan respon siswa 91%. Tingkat efektifitas e-modul berada pada kategori ‘cukup efektif’ dengan hasil uji efektifitas pemahaman siswa diperoleh rata-rata nilai tes awal = 41,2 tes akhir = 79,36, selisih skor tes awal dan akhir = 38,16. Hasil perhitungan n-gain score ialah 0.649573338 dengan presentasi sebanyak ialah 65%. Sehingga e-modul pembelajaran bahasa Arab berbasis kotekstual pada materi al-‘unwānu cukup efektif digunakan untuk meningkatkan pemahaman siswa.